Analisis Kohesi dan Koherensi Wacana Bahasa Inggris - Syahreni Siregar (Jurnal Dewantara, 2019)
A good writing has cohesion and coherence. The sentences and word are used have to be related each other and also the one meaning with the other meaning related each other. So cohesion and coherence is the main aspect in a text. The aim of this research is to know how far the students are able to analyze cohesion and coherence of English text, especially in using lexical cohesion as one of the difficulties. In this writing the data collecting method used a content anaysis, documenttion, and interview. There are 25 students’ work sheets of sixth semester of TBI STAIN Jurai Siwo Metro Academic Year 2015/2016. In this research an analysis has been conducted showed that many students still have lack of understanding at synonim, Hyphonym, Meronym, Equivalence, and Antonym. Students’ performance in analyzing the types of lexical cohesion are repeatation 75%, synonim 41%, Equivalence 22%, Meronym 15%, Hyphonim 9% and antonym 4%. This result of the research influenced the analyzing of coherence of the text. The result of this research concluded that the students of TBI STAIN Jurai Siwo Metro need more understanding in using cohesion and coherence in a text. Because there are the reltionship between cohesion and coherence. So the stedents are hoped to be able in understanding the readable and meaningfull of text.